Literature Review: Data Management, Data Analytics, and Business Intelligence for Organization - Eka Novalia Pusparini; Agussalim Agussalim (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This study was conducted to examine the functions of data management, data analytics, and business intelligence across various organizational sectors. A literature review was performed to gain a broader understanding of the topic, utilizing research backgrounds from different countries, with ten studies selected for review from multiple sources. The results indicate that efficient data management, combined with robust analytical capabilities and business intelligence tools, is crucial for modern organizations seeking to achieve operational excellence and strategic growth. By implementing the appropriate measures, organizations can maximize the benefits of data management, data analytics, and business intelligence in attaining their strategic objectives.